Role and genetic basis of specialised secondary metabolites in Trichoderma ecophysiology. (March 2022) - Vicente, Isabel; Baroncelli, Riccardo; Hermosa, Rosa; Monte, Enrique; Vannacci, Giovanni; Sarrocco, Sabrina
Abstract: Species of fungal genus Trichoderma are characterized by a versatile lifestyle, high adaptability to the changing environmental conditions and the ability to establish sophisticated interactions with other organisms. Due to their ability to antagonize plant pathogens and to elicit the plant defence responses against biotic/abiotic stresses, Trichoderma spp. are commonly used as commercially biopesticides and biofertilizers. The Trichoderma success in the rhizosphere is supported by a wide arsenal of specialised metabolites (SMs) providing morphological and physiological autoregulation, self-protection and facilitating fungal communication. This review aims to explore the roles of SMs in the biology of fungi, with special emphasis on the genus Trichoderma and on how divergence in the SMs genetic structure determine Trichoderma lifestyles. Trichoderma genomes are endowed with a high number of SMs biosynthetic genes, and understanding the genetic basis of their biosynthesis is crucial for determining the role of these metabolites in Trichoderma ecophysiology and for expanding their application in crop protection. Recent advances on the characterization of the Trichoderma SMs genetic inventory driven by computational biology are discussed. Graphical abstract: Image 1 Highlights: Secondary metabolites are messengers in fungal communication and stress tolerance The diversity of Trichoderma lifestyles is supported by their secondary metabolites Broad-function bioactive molecules support Trichoderma success in the rhizosphere Ecologic divergences influence the genetic structure of Trichoderma metabolomes